2021
DOI: 10.1080/14756366.2021.2000404
|View full text |Cite
|
Sign up to set email alerts
|

TNP and its analogs: Modulation of IP6K and CYP3A4 inhibition

Abstract: Inositol hexakisphosphate kinase (IP6K) is an important mammalian enzyme involved in various biological processes such as insulin signalling and blood clotting. Recent analyses on drug metabolism and pharmacokinetic properties on TNP ( N 2 -( m -trifluorobenzyl), N 6 -( p -nitrobenzyl)purine), a pan-IP6K inhibitor, have suggested that it may inhibit cytochrome P450 (CYP450) enzymes and induce u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In addition, modification at N 9 was included in examples 45 and 46 ( Table 6 ). Note that several of these compounds were previously reported in studies of human IPKs as well as other enzyme targets [ 34 , 35 , 37 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, modification at N 9 was included in examples 45 and 46 ( Table 6 ). Note that several of these compounds were previously reported in studies of human IPKs as well as other enzyme targets [ 34 , 35 , 37 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…TNP is an ATP-competitive inhibitor of all three IP6K isoforms in mammalian cells [ 33 ] and was discovered through a purine-based compound library screen against human IP3K [ 34 ]. However, TNP was later found to be more potent against IP6K, with an IC 50 of 0.47 µM [ 33 ] compared to an IC 50 of 10 µM against IP3K [ 34 ], and demonstrated anti-obesity and anti-diabetic effects in a mouse model of high fat diet-induced obesity [ 28 , 35 ]. Although TNP is a potent inhibitor of human IP6K, it does not inhibit rat IPMK at a concentration of 10 µM [ 36 ] and its inhibitor properties against human IPMK have not been determined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A small-scale study on individuals with insulin resistance found that IP6K1 levels (protein and mRNA) deceased under conditions of high intensity exercise that correlated with improved insulin signaling, supporting an antagonistic role for insulin signaling by IP6K1 in humans [ 54 ]. While work is ongoing to create a specific IP6K1 inhibitor for the treatment of insulin resistance this may prove difficult, as IP6K1 is also important in the regulation of phosphate homeostasis [ 55 , 56 ], which is discussed in more detail in a later section.…”
Section: The Inositol Phosphate Systemmentioning
confidence: 99%